Minors who migrate alone. Analysis of the files of child protection in Aragón. - Monterde, Chabier Gimeno (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
The research analyzes statistical data on minors who are migrating alone and are under institutional care in Aragón, between 2000 and 2010: A group of male adolescents, between fifteen and seventeen years old, migrating from North and Sub Saharan. Migrations have had three periods. The fi rst one has had few files. The next one, between 2006 and 2008, when their number increased signifi cantly, a last one, until today, when arrivals have decreased and the origins of these are more diversifi ed. The subsequent data contrasted with interviews and other documentary sources concludes that studied fi les don’t report on other unaccompanied minors who arrived at Aragón too: ones who arrived there during the fi rst years and run away from care centers as soon as possible, as well as minors who weren’t detected, remained «invisibles».